Advanced materials for solar energy harnessing and conversion - Liu, Jian (2016)
© 2016 by Taylor & Francis Group, LLC. All rights reserved. This chapter describes mainly the recent progress of the artificial photosynthesis-the way for mimicking natural counterpart to solve our current energy and environmental dilemma. It involves design and the architecting of advanced nanomaterials for light harvesting and light energy conversion purposes. The chapter incorporates interdisciplinary and diversified efforts from physicists, chemists and biologists for contributing to artificial photosynthesis research and development. Further development in the field will be of broad interests to related physicists, chemists, and biologists. Readers will gain insight into diversified routes to construct advanced light harvesting and conversion systems including conventional semiconductor engineering, morphology sculpture, reminiscent of bio-system, tandem system designs, etc. The proposed chapter targets college students, graduate and PhD students who are interested in recent advances on artificial photosynthesis. Postdoctoral students, some independent researchers and even some early-career research scientists are also listed as target readers of the proposed chapter.